(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
It has been said that Criminal Law is violence not only because of what it punishes, but also because of the way it does it. Violence is present in all human relationships,and as such, it is consubstantial to every system of social control. In spite of it,the failure of imprisonment has not been its severity, but its inefficiency regarding social rehabilitation. This lack of efficiency can be palliated through the use of alternative systems of electronic surveillance in the penitentiary context. These alternative systems will not only enable an effective solution to the problem of overcrowded prisons, but will also mitigate the harmful effects of prison. Moreover, these alternative systems represent a good method to prevent future aggressions as well as to facilitate the offender’s social rehabilitation. From this point of view, we will first explain the programs of electronic surveillancein Spain and secondly we will evaluate them in terms of social rehabilitation,cost-benefit analysis, human rights restrictions, privatization and overcrowding inprisons.